Dynamics of Entrepreneurial Actors: A Study of Economic Conditions and Psychological Capital - Suharto; Soni Suardi; Eliagus Telaumbanua; Andika Isma (CV. Sakura Digital Nusantara, 2024)
This study aims to determine the dynamics of entrepreneurs through the reasons why people choose entrepreneurship in Anabanua Village, Maniangpajo Subdistrict, Wajo Regency and the economic conditions of the people of Anabanua Village, Maniangpajo Subdistrict, Wajo Regency from the perspective of psychological capital. This research uses a qualitative method taking the research location in Anabanua Village, Maniangpajo District, Wajo Regency. Determination of subjects and informants in this study is by using the snow ball technique. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is qualitative data analysis. The results showed that the economic conditions of entrepreneurial actors in Anabanua Village, Maniangpajo Subdistrict, Wajo Regency have high psychological capital so that economic conditions in the family have the potential to increase. However, there is one informant who has a psychological capital problem, namely low self-efficacy so that economic conditions in the family have the potential to decline. Factors that are the reason for choosing entrepreneurship in addition to encouragement from parents is also one of the factors of low education levels and entrepreneurs are the backbone of the family who want to prosper the family.